DEVELOPMENT OF CYBERCRIME AND INDONESIAN CRIMINAL LAW - Kadir, Syukron Abdul; Hartanto, Hartanto (fakultas hukum universitas PGRI Semarang, 2025)
The advancement of information technology and technology has a positive impact, but can also be exploited by (cyber) criminals to carry out their evil intentions, with the potential to cause many victims and spread quickly. Crimes that use or are related to computers and the internet can make a place in cyberspace (computers/internet) a means to commit evil deeds, a target/target of crime, or a place to hide the proceeds of crime. The research method used is a normative research method with a descriptive model that examines aspects of legal regulations related to cybercrime and its development. The results of the study show that the development of computer crime today is not only limited to illegal access, and at a low level has disrupted social relations between communities with the type of defamation/hoax. Further development of the scope of crime and cybercrime requires sophisticated tools for law enforcement, as well as the professionalism of law enforcers. In addition to the criminal law system and imprisonment for cyber criminals, another alternative is restorative justice for low-level crimes. The government